2017
DOI: 10.1080/10810730.2016.1261970
|View full text |Cite
|
Sign up to set email alerts
|

Does Health Information in Mass Media Help or Hurt Patients? Investigation of Potential Negative Influence of Mass Media Health Information on Patients’ Beliefs and Medication Regimen Adherence

Abstract: As an important public health issue, patient medication non-adherence has drawn much attention, but research on the impact of mass media as an information source on patient medication adherence has been scant. Given that mass media often provide confusing and contradicting information regarding health/medical issues, this study examined the potential negative influence of exposure to health information in mass media on patients' beliefs about their illnesses and medications, and medication adherence, in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
0
34
0
1
Order By: Relevance
“…The opportunity to encounter conflicting information also increases when information is obtained from more than one source of information (e.g., a healthcare provider and the internet; Carpenter et al, 2010Carpenter et al, , 2014. This is likely to confuse patients and may potentially lead to misunderstanding, negative beliefs about medication, and consequently, negative health behaviors such as lower medication adherence (Im & Huh, 2017;Nagler, 2014). This is particularly problematic for patients experiencing difficulties in estimating the credibility of online health information (Carpenter et al, 2014).…”
Section: Patients' Online Information Seeking Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…The opportunity to encounter conflicting information also increases when information is obtained from more than one source of information (e.g., a healthcare provider and the internet; Carpenter et al, 2010Carpenter et al, , 2014. This is likely to confuse patients and may potentially lead to misunderstanding, negative beliefs about medication, and consequently, negative health behaviors such as lower medication adherence (Im & Huh, 2017;Nagler, 2014). This is particularly problematic for patients experiencing difficulties in estimating the credibility of online health information (Carpenter et al, 2014).…”
Section: Patients' Online Information Seeking Behaviormentioning
confidence: 99%
“…In total, 200 determinants of medication adherence have been studied but none of them has been consistently related to adherence (Donovan, 1995). Research on the impact of the internet on medication adherence is rare (Im & Huh, 2017). A recent study showed that almost all chronic patients use the internet to make decisions about their medication (Feathers et al, 2016).…”
Section: Medication Adherence and The Internetmentioning
confidence: 99%
See 3 more Smart Citations